2011
DOI: 10.1016/j.anorl.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Interest of fine-needle aspiration cytology in thyroid nodule

Abstract: The main pitfall of FNAC in thyroid pathology is the "suspect" category, for which positive diagnosis is founded on histological criteria alone. The second limitation identified in this study was the high number of "unrepresentative" aspirates. However, the technique remains useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
5
0
3
Order By: Relevance
“…Salivary gland tumors, because of their diversity, till date continue to hold the interest of the surgeons and the pathologists. Although fine needle aspiration cytology (FNAC) is now part of routine clinical practice for the evaluation of thyroid tumors[ 1 ] and cervical lymph nodes, no consensus has been reached concerning the role of this procedure in the management of salivary glands lesions, as some authors consider that it has a low sensitivity for diagnosis of malignant salivary tumors. [ 2 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Salivary gland tumors, because of their diversity, till date continue to hold the interest of the surgeons and the pathologists. Although fine needle aspiration cytology (FNAC) is now part of routine clinical practice for the evaluation of thyroid tumors[ 1 ] and cervical lymph nodes, no consensus has been reached concerning the role of this procedure in the management of salivary glands lesions, as some authors consider that it has a low sensitivity for diagnosis of malignant salivary tumors. [ 2 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…malignancy rate in this category was 29.2% (6 cases were PTC and one case of FTC), the remaining nodules proved to be benign (6 lymphocytic thyroiditis, 8 follicular adenomas, 2 Hürthle cell adenomas, and one case of subacute thyroiditis). Consequently, these results made a low malignancy rate, this rate was lower than other studies [13][14][15][16], but a lower malignancy rate was seen in some series [20].…”
Section: Bethesda Category N (%) This Seriesmentioning
confidence: 51%
“…Finally, FNA accuracy parameters differ among different studies according to the categories included as a positive for malignancy, some studies [13][14][15]20] included indeterminate cytology, while our study and others [24] did not. False positive results lowered specificity in our study to 79.35% compared with other studies (68.4%-97.6%), results are summarized in table 4, with a sensitivity of 85% compared with (94.2%-100%), and total accuracy of 80.36% while other studies reported the accuracy of (85.14%-97%).…”
Section: International Journal Of Endocrinology and Metabolic Disordersmentioning
confidence: 60%
“…It is increasingly being introduced into everyday clinical practice also in our region (Mures County, Romania). Its use is well established in the management of thyroid nodules [2] [4] , and it gains more and more popularity also in other fields of medicine such as the evaluation of breast lesions, head and neck masses, and in general superficial and deep lesions [5] – [11] . Diagnosis is based on the interpretation of cytological material aspired with a small diameter needle.…”
Section: Introductionmentioning
confidence: 99%